2023
DOI: 10.3390/rs15133447
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Different Important Predictors and Models for Estimating Large-Scale Biomass of Rubber Plantations in Hainan Island, China

Abstract: Rubber (Hevea brasiliensis Muell.) plantations are among the most critical agricultural ecosystems in tropical regions, playing a vital role in regional carbon balance. Accurate large-scale biomass estimation for these plantations remains a challenging task due to the severe signal saturation problem. Recent advances in remote sensing big data, cloud platforms, and machine learning have facilitated the precise acquisition of key physiological variables, such as stand age (A) and canopy height (H), which are cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 73 publications
0
2
0
Order By: Relevance
“…To alternatively inform the related stockholders, accurate and rapid mapping aimed at estimating sugarcane AGB and carbon stock quantification is useful. The studies of Mansaray et al [17], Wang et al [18], Wang et al [19], and Li et al [20] have shown highly accurate mapping of crops AGB (i.e., rice, sugarcane, graze, and rubber tree) using multiple remote sensing data and powerful machine learning regression models. Therefore, satellitebased Earth Observation (EO) data can offer valuable information on wide geographical areas in a timely and cost-efficient manner.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To alternatively inform the related stockholders, accurate and rapid mapping aimed at estimating sugarcane AGB and carbon stock quantification is useful. The studies of Mansaray et al [17], Wang et al [18], Wang et al [19], and Li et al [20] have shown highly accurate mapping of crops AGB (i.e., rice, sugarcane, graze, and rubber tree) using multiple remote sensing data and powerful machine learning regression models. Therefore, satellitebased Earth Observation (EO) data can offer valuable information on wide geographical areas in a timely and cost-efficient manner.…”
Section: Introductionmentioning
confidence: 99%
“…Uribeetxebarria et al [43] combined S1 and S2 data to estimate wheat biomass and yield in the Llanada Alavesa region in northern Spain, obtaining high accuracy with R 2 = 0.95 and RMSE = 0.2 t/ha. In addition, Li, Wang, Gao, Wu, Cheng, Ren, Bao, Yun, Wu, and Xie [20] also mapped the biomass of rubber plantations in Hainan island, China, using S2 and Landsat data, achieving high accuracy (R 2 = 0.97 and RMSE = 7.7 × 10 −9 t/ha). Their results proved highly accurate with excellent mapping crop biomass based on combining multi-temporal S1 and S2 satellites and the great machine learning regression methods.…”
Section: Introductionmentioning
confidence: 99%
“…The results of vegetation classification have a direct impact on forest biomass [20], which serves as an indicator of energy accumulation in the production and metabolic processes of an ecosystem within a specific area. It is a crucial indicator that reflects the structural and functional characteristics of the forest ecosystem, as well as its development potential [21]. These results hold significant practical significance for the scientific management and economic development of forested lands [22].…”
Section: Introductionmentioning
confidence: 99%
“…Forests play a vital role in the land ecosystem of the Earth. They are indispensable for conserving biodiversity, protecting watersheds, capturing carbon, mitigating climate change effects [1,2], maintaining ecological balance, regulating rainfall patterns, and ensuring the stability of large-scale climate systems [3,4]. As a result, the timely and precise monitoring and mapping of forest cover has emerged as a vital aspect of sustainable forest management and the monitoring of ecosystem transformations [5].…”
Section: Introductionmentioning
confidence: 99%